2022
DOI: 10.1051/0004-6361/202142854
|View full text |Cite
|
Sign up to set email alerts
|

Radio properties of the OH megamaser galaxy IIZw 096

Abstract: Based on the two-epoch European Very Long Baseline Interferometry (VLBI) Network (EVN) archive data from OH line observations of IIZw 096, we confirm that the high-resolution OH emission in this source mainly comes from two spots (OH1 and OH2) of component (comp) D1 of this merging system. We found no significant variations in the OH 1667 MHz line emission, including flux densities and peak positions. The OH 1665 MHz line emission is detected at about the 6σ level in the OH1 region by combining two epochs of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Although ID 7 (D0) is the brightest source at 1.6 μm, the JWST mid-IR data demonstrate that ID 8 (D1) generates the bulk of the total IR emission in IIZw096. The location of ID 8 also coincides with two OH megamasers (Migenes et al 2011;Wu et al 2022). 34 Megamasers are often found in merging (U) LIRGs, in close proximity to the nuclei (e.g., Roberts et al 2021), marking regions of extremely high gas density and strong far-IR radiation.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Although ID 7 (D0) is the brightest source at 1.6 μm, the JWST mid-IR data demonstrate that ID 8 (D1) generates the bulk of the total IR emission in IIZw096. The location of ID 8 also coincides with two OH megamasers (Migenes et al 2011;Wu et al 2022). 34 Megamasers are often found in merging (U) LIRGs, in close proximity to the nuclei (e.g., Roberts et al 2021), marking regions of extremely high gas density and strong far-IR radiation.…”
Section: Discussionmentioning
confidence: 56%
“…The diffuse, extended emission around ID 8 would then be the remnants of the third galaxy's disk. The estimated stellar mass of ID 8 is ∼10 9 M e and there is a similarly large mass of gas in this region (Inami et al 2010;Wu et al 2022). These estimates might indicate ID 8 is a partially stripped third nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here we tentatively classify this region as an extranuclear "SF" following Inami et al (2010). We note that while VLBI observations of the OH megamaser in this region have suggested that it may host an obscured AGN (Migenes et al 2011), recent multifrequency analysis of the radio spectrum shows that it is well described by pure star formation (Wu et al 2022). 60.…”
Section: Appendix a Notes On Individual Systemsmentioning
confidence: 65%